Intelligent control for computer integrated manufacturing - Mohamed, Y.; Liu, L.; Elbestawi, M.A.; Sinha, N.K. (Proceedings of the 27th IEEE Conference on Decision and Control, 1988)
An intelligent machining controller is developed for cutting-force regulation of the peripheral milling process. This controller combines parameter adaptive control algorithms(s) with heuristic logic, which monitors the performance of the control algorithms. The development of knowledge and rule bases for intelligent control is discussed, and the resulting improvements in control performance are demonstrated using real-time experiments.< >